1990
DOI: 10.1029/jd095id12p20507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autocorrelation and temporal sampling schemes on estimates of trend and spatial correlation

Abstract: This paper is concerned with temporal data requirements for the assessment of trends and for estimating spatial correlations of atmospheric species.We examine statistically three basic issues:(1) the effect of autocorrelations in monthly observations and the effect of the length of data record on the precision of trend estimates, (2) the effect of autocorrelations in the daily data on the sampling frequency requirements with respect to the representativeness of monthly averages for trend estimation, and (3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
289
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(299 citation statements)
references
References 19 publications
7
289
0
3
Order By: Relevance
“…We have compared errors (i.e. standard deviations) in regression coefficients derived using this bootstrap method with standard MLR errors calculated using an autocorrelation model of type AR1 (Tiao et al, 1990). For our long time series, typically more than a decade, standard deviations derived with the bootstrap method are found to be in excellent agreement with MLR standard errors.…”
Section: Multiple Regression Modelsupporting
confidence: 50%
See 2 more Smart Citations
“…We have compared errors (i.e. standard deviations) in regression coefficients derived using this bootstrap method with standard MLR errors calculated using an autocorrelation model of type AR1 (Tiao et al, 1990). For our long time series, typically more than a decade, standard deviations derived with the bootstrap method are found to be in excellent agreement with MLR standard errors.…”
Section: Multiple Regression Modelsupporting
confidence: 50%
“…Overall, this approach was providing satisfactory results in most cases. However, it was found not to be robust for short time series when errors could be vastly underestimated (Tiao et al, 1990). As a result, we tested the bootstrapping approach; we found that it provided results (regression coefficients, associated errors) results that were close to the results obtained with the Cochrane-Orcutt approach for most cases.…”
Section: Multiple Regression Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…[21] The determination of the number of years needed to detect a long-term linear trend of a given magnitude has been extensively studied by Tiao et al [1990] and Weatherhead et al [1998Weatherhead et al [ , 2000. This number of years increases with the magnitude of the variance (s N 2 ) and the autocorrelation coefficient (f) of the data noise.…”
Section: Least-mean-square Fitmentioning
confidence: 99%
“…2.2) to remove all known sources of variability, ω 0 is the trend magnitude in K year −1 (see Fig. 6), and φ N is the autocorrelation in the residuals (Tiao et al, 1990). This equation implies that, after the calculated number of years, there is a 90 % probability that a trend of the correct sign will have been detected, if we assume that detecting a trend means identifying a trend at the 95 % confidence level.…”
Section: Site Selection For Temperature Trend Detectionmentioning
confidence: 99%